Prevod kot interpretacija - Kocijančič-Pokorn, Nike (Primerjalna književnost, 2000)
Translation as interpretation: Hiša Marije Pomočnice by Henry Leeming. - Although hermeneutic philosophers argue that every translation is an interpretation, a specific reproduction of the original, translation reviews in Slovenia rarely, if ever, attempt to disclose the translator's interpretations of the original text. Reviewers usually focus on the translator's style and neglect all other changes and more radical shifts that occured during the translation provess, not only in translations that claim tobe free interpretations or even adaptations, but also in those allegedly faithful to the original text; this is the case in translations both from and into Slovene. A translational interpretation of an original text is exemplified by an analysis of the translation into English by Henry Leeming of one of the classic texts of Slovene literature, Ivan Cankar's Hiša Marije Pomočnice. - Leeming's remodelling of the original text was consistent with his reading of Hiša Marije Pomočnice as an essentially naturalistic work. In the original there exist three worlds: the morally depraved world of the city, the transient world of the hospital, and the much desired and luminous world following death. In Leeming's translation, the world desired by the girls partially overlaps with the world outside the hospital walls; the translator thus offers a reading which alters and moderates the hostile rejection of the "real" life of the city found in the original text. Another distinctive feature of this translation is omission, especially the omission of five paragraphs in charpter seven, which alters the impressionistic and religious nature of the text. Leeming seemed to have read Hiša Marije Pomočnice primarily as a naturalistic and not as an impressionistic, neo-romantic work with strong religius overtones, and has translated it in line with his interpretation. The translation not only shows his reading of the original; the omission and translational shifts also reveal the complexity of the original and possible new interpretations of it.
Keywords: Cankar, Ivan: Hiša Marije Pomočnice; interpretacije; Leeming, Henry, 1919-; literarne študije; prevodi; Slovene literature; slovenska književnost